Agrochemical protection practices for market gardeners and environmental risks on farms in Bouira (Northern Algeria) - Bachouche Nassima; Lamri Naziha; Berghout Karima; Oultaf Lynda; Metna Ali Ahmed Fatiha; Bourfiss Nassima; Akkouche Saida (Glasnik Srpskog Geografskog Društva)
Pesticides are used to protect crops against natural enemies. However, poor management of these products harms the environment and public health. The study aims to assess the use of pesticides on market garden crops in the Bouira region. We surveyed them to obtain as much information as possible and to identify current pesticide use practices for the varieties of plants grown in the region. We were able to determine 23 commercial brands, including 21 active ingredients. All the farmers interviewed used different types of pesticides, with rates of 84% for fungicides, 76% for insecticides, 44% for herbicides, and 20% for acaricides. When applying these products, farmers do not protect themselves properly; only 24% use the full kit. The management of empty packaging is haphazard. Most farmers (46%) burn empty packaging, 28% choose to deposit it in landfill sites, and 8% abandon it on their farms. Our results indicate the use of several active ingredients and a lack of respect for the rules of good agricultural practice.